A personal assistant for health care professionals based on clinical protocols - Oliveira, T. (2016)
Current tools to operationalize Computer-Interpretable Guidelines focus mainly on displaying recommendations rather than assisting health care professionals in their daily activities. Furthermore, their underlying models have limitations at the level of temporal representation that hinder the accurate depiction of clinical protocols in a few specific situations. This work identifies such situations and proposes a comprehensive temporal model based on OntologyWeb Language (OWL), along with a web-based tool that provides an alternative way to deploy and view clinical protocols. This is evaluated through a case study featuring a clinical protocol for the treatment of colon cancer. It was possible to observe that the model was able to represent the majority of temporal patterns, specially those with periodic events and temporal restrictions about the state of a patient.